Modernisasi dan Transformasi Seni Lukis Bali pada karya I Gusti Nyoman Lempad - I Wayan Seriyoga Parta (Ars: Jurnal Seni Rupa dan Desain, 2010)
Pita Maha was founded by Cokorda Gede Raka Sukawati, with Walter Spies and Bonnet Rodelf  in. Pita Maha as an organization that embodies activity Balinese painters and sculptors at that time, 1937th contribute to the marketing of  art works. Through this Pitamaha values-aesthetic identity Balinese art and artists built awareness (constructed), then be the names then began confirmed its position as an individual artist.  So the position of  an artist for most of  Balinese painters at that time was in a state of  given situation, rather than grow out of  their consciousness as an individual artist (modern). Although the development is slowly starting to appear professional awareness of  the individual artists but again, awareness is not as modern individual artist. I Gusti Nyoman Lempad is one of the most important generation of  artists Pita Maha, displaying his works of  art aesthetic transpormasi postHindu Balinese to fine art (painting) modern Balinese.Keywords: Pita Maha, aesthetic, transformation, indivial artist, visual art (Bali)